Proces konstytucyjny na Ukrainie w latach 1990–2006 - Czubara, Tomasz (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
This paper attempts to describe the constitution process in Ukraine from 1990 to 2006, given the dispute between the President and the Highest Council (Parliament). The transformations of post-soviet republics that followed the collapse of the USSR created a need for new political, social and economic agreements to be drawn up to befit the new times. The reforming process of these realms of Ukrainian society’s activity was reflected in the evolution of Ukrainian constitutional principles. The Ukrainian Constitution determines the political and administrative system of the state. The amendments proposed have favored either the President or the Highest Council, depending on the political situation in the country. Despite numerous attempts, the most important reforms of the system have still not been implemented in Ukraine, which is hardly conducive to the state’s stability. The emergence of the foundation for the political system of the independent Ukrainian state is a good illustration of how individual interests of different political forces exert a negative impact on the shaping of a civic society and local self-government, based on transparent principles.